(untitled) (Journal of National Institute of Ophthalmology, 2022)
Background: The Oculocardiac reflex (OCR) is a well-known complication of ocular surgery involving direct or indirect manipulation of the eye or ocular adnexa. While most commonly associated with eye muscle surgery, with a reported incidence of 40-93%, it is prevalent during traction on the extraocular or eyelid muscles, compression of the globe, intraocular and retro bulbar injection, iris traction, retinal reattachment surgery and enucleation procedures and may manifest as a wide range of arrhythmias including ventricular bigeminy, bradycardia and asystole. Occurrence of the reflex in eye muscle surgery has been documented to increase with hypoxia and decrease with aging and premedication with anticholinergics, namely glycopyrrolate or atropine. Objective: The purpose of our study was to determine the degree of change in heart rate (HR) and systolic blood pressure (SBP) during Enucleation surgery in patients anaesthetized with equipotent concentrations of Isoflurane or Halothane breathing via a laryngeal mask airway (LMA). Methods: The study was designed as a prospective randomizedstudy. Fifty patients, having selected for Enucleation were randomized to Isoflurane (I) or halothane (H) in 66% nitrous oxide at 1.3 minimum alveolar concentration. Patients breathed through a laryngeal mask airway (LMA) and were not pretreated with anticholinergics. Results: The Oculocardiac reflex (OCR), defined as a 20% decrease in heart rate (HR) from baseline, dysrhythmias or sinoatrial arrest concomitant with ocular muscle traction occurred less frequently with Isoflurane than with halothane (I: 37%, H:78%, P = 0.009). The HR during induction was higher with Isoflurane (I: 110 ± 13 bpm, H: 100 ± 15 bpm, P = 0.002). The lowest HR occurred with halothane (I: 94 ± 22 bpm, H: 72 ± 19 bpm, P = 0.001). The incidence of dysrhythmias was higher in the halothane group (I 4%, H: 42%, P = 0.004). Isoflurane may be a more suitable anaesthetic than halothane for operations involving traction on the ocular muscles with controlled respiration in patients because of reduced incidence of OCR with slightly higher airway irritability. Conclusion: Some patients experience a sudden slowing of the heart when the surgeon pulls on the eye muscles during Enucleation operations under anaesthesia. We found that Isoflurane was associated with a lower incidence of the OCR but relatively higher airway irritability compared with halothane. The oculocardiac reflex possesses the potential for significant morbidity and mortality. While some have documented factors affecting the OCR during eye muscle surgery, our data could not prove such a relationship during enucleation. J. Natl. Inst. Ophthalmol. 2022;5(1):21-26